Corporate Governance Characteristics: What Affects Forward-Looking Information Disclosure? - Eny Kusumawati; Susilaningdyah Mustikawati (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: The purpose of this study is to analyze the effect of five corporate governance characteristics on forward-looking information disclosure (FLID) in non-financial companies listed on the Indonesia Stock Exchange during the period 2021–2023. The characteristics analyzed include the existence of a risk management committee, political connections, directors' educational background, gender diversity, and the frequency of board meetings Methodology/approach: This study employed a quantitative approach, utilizing secondary data from annual reports. The sampling technique used was purposive sampling. Data analysis used panel data regression with the help of Eviews13. Findings: The study found that the frequency of board meetings significantly influenced FLID. Conversely, the risk management committee, political connections, directors' educational background, gender diversity, did not influence FLID. Practical implications: This study contributes to the corporate governance literature in Indonesia and recommends strengthening the active role of internal governance in promoting information disclosure. Originality/value: The novelty of this research lies in the simultaneous testing of five characteristics of corporate governance with an emphasis on risk management committees and political connections, two variables that have rarely been studied together, especially in Indonesia